Effects of the fixed-dose combination therapy with indapamide and valsartan on renal function in patients with Type 2 diabetes mellitus and arterial hypertension - T. V. Malykh; A. P. Babkin (Кардиоваскулярная терапия и профилактика)
Aim. To study the effects of the fixed-dose combination antihypertensive therapy (noliprel A forte, valsaforce, and indapamide) and the renal function dynamics in patients with Type 2 diabetes mellitus (DM-2) and arterial hypertension (AH). Material and methods. In total, 40 patients with DM-2 and AH were randomised into two groups: Group I received noliprel A forte, and Group II received valsaforce and indapamide for two months. The clinical effectiveness of the fixed-dose combination antihypertensive therapy was assessed by 24-hour blood pressure monitoring (BPM), blood biochemistry, and renal function parameters measured at baseline and 8 weeks after the start of the treatment. Results. The treatment was associated with a substantial reduction in BP levels, improved circadian BP profiles, and metabolic neutrality. The therapy with noliprel A forte resulted in markedly improved circadian BP profiles and renal function, as demonstrated by the microalbuminuria dynamics (Rehberg-Tareev test: by 11±0,56 ml/min; Cockgroft-Gault formula: by 12±0,36 ml/min; MDRD formula: by 10±0,16 ml/min/1,73 m2). Conclusion. In patients with DM-2 and AH, the therapy with noliprel A forte significantly improved renal function parameters.